Myanmar Migration Assessment: Note on Dataset - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
The population of Myanmar is becoming increasingly vulnerable due to political instability, armed conflict, economic disruptions, price volatility, and climatic shocks. Migration has emerged as one of the few viable pathways to potentially improve household welfare amid these challenges. However, whether migration can indeed deliver some relief depends on the ability of migrants to find safe, well-paid jobs despite financial barriers and other challenges. The Myanmar Migrant Assessment (MMA) interviewed a sub-sample of the Myanmar Household Welfare Survey (MHWS), who either have a household member who has migrated or attempted to migrate in the previous 10 years (since 2013) or has relocated their entire household since February 2021, to better understand the process and consequences of migration. The survey interviewed 4,296 households by phone between June 8 – July 14, 2023. In this note, we provide details on data collection and sample design for the MMA as well as give an overview of the survey modules.